Professional And Personal Characteristics of Leadership Individually Leadership - Elmurodov Ulug’bek Yusup og’li (Zien Journals, 2022)
The article analyzes the work done in the leadership and management system, theoretical and practical aspects of leadership psychology in the new era of management psychology
Keywords: Management; leadership; professional competence; subject leader